How did three consecutive matches with extra time affect physical performance? A case study of the 2018 football Men’s World Cup - Kołodziejczyk, Michał; Chmura, Paweł; Milanovic, Luka; Konefał, Marek; Chmura, Jan; Rokita, Andrzej; Andrzejewski, Marcin (Biology of Sport, 2021)
The purpose of this study was to ascertain the effect of playing three consecutive matches with extra time (ET) on the physical performance of selected Croatian players in their subsequent match, the final of the 2018 Men’s World Cup in Russia. The case study consisted of 4 players on the Croatian national team (16 observations) who had played in all three matches up to 120 min. The consecutive full time matches (90 minutes) and extra time (30 minutes) were compared. The analysis was conducted using data collected by an advanced motion analysis system known as STATS and from interviews with the strength and conditioning coach of the Croatian national team. The recorded variables used were: total distance covered [m], distances covered [m] at intensity ranges of 20–25 km/h and above 25 km/h, and number of sprints performed. All the studied parameters systematically increased in each match up to 90 minutes of play, reached their maximum values in the semi-final and then decreased in the final match. Compared to the first extra time period, in the third extra time period the players covered twice as much distance with an intensity of 20–25 km/h and above 25 km/h, and recorded twice as many sprints. This investigation shows that players in central positions on the pitch are able to maintain or even increase high and very high intensity activity in three consecutive matches with extra time. These data complement the developing body of literature relating to the influence of accumulation of match play with extra time periods on high level players.